Estudio morfo-decorativo en la cerámica de la Plataforma Uhle, año 2017 Huaca de la Luna, Valle de Moche - Narcizo Zavaleta, Sara Esther (2022)
Ten tombs of the Mochica III and IV styles from the Uhle Platform of Huaca de la Luna have been selected, with the purpose of studying the ceramics associated with the burials. Our research has allowed us to examine the morphology and decoration of ceramics both in their stylistic phases as well as recurring and prominent motifs, as well as the shape categories of the most common vases. Studying ceramics associated with burials leads us to a more sophisticated ceramic style with a finer finish due to the character and function of these elite funerary contexts in Huaca de La Luna. While it is true that the study of ceramics allow us to study the Moche society, within which being the specialists or artisans potters linked to elaborate more representative vessels for the elite characters that were part of the ruling class.